Synchronous Neural Oscillation Between the Right Inferior Fronto-Parietal Cortices Contributes to Body Awareness - Takeuchi, Naoyuki; Sudo, Tamami; Oouchida, Yutaka; Mori, Takayuki; Izumi, Shin-Ichi (Frontiers in Human Neuroscience, 2019)
The right inferior fronto-parietal network monitors the current status of the musculoskeletal system and builds-up and updates our postural model. The kinesthetic illusion induced by tendon vibration has been utilized in experiments on the modulation of body awareness. The right inferior fronto-parietal cortices activate during the kinesthetic illusion. We aimed to determine the relationship between the right inferior fronto-parietal cortices and body awareness by applying transcranial alternating current stimulation (tACS) to exogenously modulate oscillatory neural activity in the right fronto-parietal cortices during the kinesthetic illusion. Sixteen young adults participated in this study. We counterbalanced the order in which participants received the three types of tACS (55 Hz enveloped by 6 Hz; synchronous, desynchronous, and sham) across the subjects. The illusory movement perception induced by tendon vibration of the left extensor carpi ulnaris muscle was assessed before and during tACS. Application of synchronous tACS over the right inferior fronto-parietal cortices significantly increased kinesthetic illusion compared with sham tACS. The kinesthetic illusion during desynchronous tACS decreased from baseline. There was no change in vibration sensation during any tACS condition. The modulation of oscillatory brain activity between the right fronto-parietal cortices alters the illusory movement perception without altering actual vibration sensation. tACS over the right inferior fronto-parietal cortices is considered to modulate the neural processing involved in updating the postural model when the stimulated muscle spindle sends kinesthetic signals. This is the first study that reveals that rhythmic communication between the right inferior fronto-parietal cortices has a causal role in body awareness.